Relevance of the World Bank Group’s Early Response to COVID-19 : A Cross-Country Sector Analysis - Naeher, Dominik; Narayanan, Raghavan; Ziulu, Virginia (Washington, DC: World Bank, 2022)
Evaluating the relevance of development interventions is a complex task because many different dimensions must be considered. This study focuses on one particular, quantifiable aspect of relevance and proposes a method for generating data-driven evidence that can be used to assess the relevance of past interventions and guide decisions about future strategic priorities. For the purpose of this study, relevance is defined as the match between the types and scopes of provided support and the types and scopes of support that are most needed in each country. The latter is estimated based on a multidimensional vulnerability score, which is constructed using data on various empirical indicators that have been argued in the economic literature to proxy vulnerability to shocks at the country level. Comparing the vulnerability score with the sector-specific allocation of support yields two empirical measures of relevance, one at the country level and one at the sector level within each country. The proposed method is designed and applied to evaluate the relevance of the World Bank Group’s early response to COVID-19. At the same time, many of the modeling insights are more broadly applicable and may also be useful in informing evaluations of development programs beyond the specific application considered here.